Academic Cheating : Dimensi Fraud Diamond Theory - Romah Wulansuci; Nujmatul Laily (Jurnal Pendidikan Ekonomi (JUPE), 2022)
The purpose of this study was to test academic cheating behavior among students by using elements of the fraud diamond, namely pressure, opportunity, rationalization, and ability. Using a simple random sampling technique, the research sample was obtained as many as 195 accounting students. This research uses a quantitative approach with the type of explanatory research. Data collection obtained by distributing questionnaires and measured using a Likert scale. Data analysis was carried out using multiple linear regression. The results shows that the elements of opportunity and ability have a significant positive effect on students' academic cheating behavior. While the element of pressure and rationalization does not affect students in committing academic fraud.